Ligational Behaviour of Vanillin Derived Schiff Bases Towards Nickel(II) and Copper(II) - TIWARI, VIVEK; SINGHAI, RASHMI (Asian Journal of Chemistry, 2010)
Complexes of Ni(II) and Cu(II) with Schiff bases, vanillidene-4 chloroaniline (VCA) and vanillidene-3-nitroaniline (VNA) have been synthesized and characterized by elemental analysis, molar conductance, magnetic measurement, IR and electronic spectra. Coordination of azomethine nitrogen in the Schiff base of the metal has been proposed. Antimicrobial activities of the complexes have also been evaluated.